Extramedullary Plasmacytoma of the Sinonasal Cavity: Magnetic Resonance Imaging Characteristics With Readout-Segmented Diffusion-Weighted Imaging and Dual-Energy Computed Tomography Features. Issue 2 (March 2022) - Duan, Fei; Wang, Peng; Qi, Meng; Wang, Yuzhe; Guo, Linying; Xiao, Zebin; Zhan, Yang; Yao, Zhenwei; Tang, Zuohua
Abstract : Purpose: To determine magnetic resonance imaging (MRI) with readout-segmented diffusion-weighted imaging (RESOLVE-DWI) and dual-energy computed tomography (DECT) features of sinonasal extramedullary plasmacytoma (SN-EMP). Methods: The MRI and/or DECT of 10 patients with SN-EMP confirmed by pathology were retrospectively reviewed. Apparent diffusion coefficient (ADC) values of RESOLVE-DWI were analyzed in 9 patients. The quantitative parameters derived from DECT, including the iodine concentration (IC), effective atomic number, and the slope (k) of spectral attenuation curve, were measured in 3 patients. Results: On conventional MRI, typical lesions were well defined (7 of 9), and isointense to the brain on both T1WI and T2WI (9 of 9). Most lesions presented with marked enhancement on contrast-enhanced T1WI without significant necrosis (8 of 9). Notably, multiple flow-void signals were observed in all lesions (9 of 9). On RESOLVE-DWI, the average ADC value was 0.55 × 10 −3 mm 2 /s, and the normalized ADC value was 0.66 ± 0.04. On DECT, the average values of IC, effective atomic number, and slope (k) was 2.7 mg/mL, 8.62, and 3.8, respectively. Conclusions: Some typical MRI features (well-defined mass, isointensity to the brain, marked enhancement without obvious cystic changes, multiple flow voids, and a lower ADC value) strongly suggest the diagnosis of SN-EMP. The quantitative parameters derived from RESOLVE-DWI and DECT may provide more information for the diagnosis of SN-EMP.